Integrating TikTok into EFL Learning: The Development of Instructional Videos for Descriptive Text - Lailiyyatur Rizqiyah; Ahmad Thoyyib Shofi (PROJECT (Professional Journal of English Education), 2026)
The purpose of the study is to develop TikTok-based instructional videos for teaching speaking of descriptive text to tenth-grade senior high school students. The study used the research and development (R&D) in the form of the ADDIE model, which contains phases for analysis, design, development, implementation, and evaluation. The participants were X-7, consisting of 32 students. The instruments used to collect the data were teacher interviews, teacher and students’ questionnaires, and validation experts as the main instruments. The results demonstrated that the media successfully engaged students’ motivation, engagement, and confidence in learning descriptive text. The videos included vocabulary, pronunciation guidance, text examples, and interactive features such as TikTok Stitch, which allowed students practice on their own and repeatedly. The significance of this study can be applied in English language teaching, particularly in speaking class for senior high school level.